The Pampean Diatom Index (IDP) for assessment of rivers and streams in Argentina - Gomez, Nora (2001)
The rivers and streams of the Pampean plain are subjected to the impact of agriculture, cattle-raising and industrialactivities. The largest urban center of Argentina is located here. The most important stresses on rivers andstreams in the Pampean plain are organic enrichments (discharge of insufficiently treated sewage), nutrients,heavy metals, pathogenic agents, pesticides, herbicides and physical changes produced by dredging and canalisation.The epipelic community is suitable for biomonitoring purposes because it allows for comparing similar substratesalong the rivers and streams. A total of 164 samples of epipelic diatoms were collected during 1995-1999 fromPampean rivers and streams. The analysis of these samples resulted in the development of a specific biotic index:the Pampean Diatom Index (IDP). The results were correlated with the main chemical water characteristics andwith other biotic indices. This study suggests that the IDP is integrating organic pollution and eutrophication andcan be applied for monitoring the biological quality of rivers and streams in the Pampean plain.